ความสัมพันธ์ระหว่างกลุ่มอาการ กลยุทธ์ในการจัดการกับอาการ การสนับสนุนทางสังคม กับคุณภาพชีวิตผู้ป่วยมะเร็งเต้านมที่ได้รับเคมีบำบัด - มาศอุบล วงศ์พรหมชัย (จุฬาลงกรณ์มหาวิทยาลัย, 2005)
To study symptom clusters, symptom management strategies, social support, and quality of life in breast cancer patients undergoing chemotherapy and the relationships between symptom clusters, symptom management strategies, social support, and quality of life in breast cancer patients undergoing chemotherapy. The theoretical framework based on symptom management model of Dodd et al. (2001). One hundred fifty breast cancer patients undergoing chemotherapy were recruited by using simple random sampling from the Out-Patients Department of Mahavajiralongkorn Cancer Center, Ramathibodi Hospital. The instruments were a pain scale, piper fatigue scale, insomnia severity index, beck depression inventory, social support questionnaires, self-care diary, and quality of life. Cronbach s alpha coefficients of all instruments were .96, .95, .89, .93, .91, .25, .36, .32,and .43, respectively. Data were analyzed using mean, standard deviation, Pearson s product moment correlation and Eta s correlation. Major findings were as follows 1. Breast cancer patients undergoing chemotherapy had perceived quality of life at a high level (Mean = 66.43, SD=13.94). 2. Symptom clusters were significantly negative related to quality of life (r = -.449, p<.05). 3. Social support was significantly positive related to quality of life (r = .201, p<.05.) 4. Self-care strategies for pain, insomnia, and fatigue were significantly negative related to quality of life (p<.05). 5. Self-care strategies for depression were not related to quality of life.